2002
DOI: 10.2166/ws.2002.0144
|View full text |Cite
|
Sign up to set email alerts
|

Use of recycled crushed glass as a filtration medium in municipal potable water treatment plants

Abstract: The aim of this study was to investigate the use of recycled crushed glass as a filtration medium for municipal potable water treatment plants. It evaluated the main physical parameters of recycled glass and its performance in a potable water treatment application. Pilot-plant testing was used to compare the performance of recycled glass to a typical sand filter medium in a conventional treatment process. Laboratory analysis was used to determine media characteristics. Pilot-plant testing determined that the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…As a result of the sedimentation applied for FP, FPA and FD, the amount of TSS decreased by 41, 88 and 97 % respectively. In FP supernatant, the amount of TSS was still greater than the permissible value and amounted to 43 mg/dm 3 . In order to remove such TSS, the washing process can be intensified, e.g.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…As a result of the sedimentation applied for FP, FPA and FD, the amount of TSS decreased by 41, 88 and 97 % respectively. In FP supernatant, the amount of TSS was still greater than the permissible value and amounted to 43 mg/dm 3 . In order to remove such TSS, the washing process can be intensified, e.g.…”
Section: Resultsmentioning
confidence: 90%
“…Due to a different mechanism of filtration and washing, in vacuum filters, the method of sampling was also different. About 1 dm 3 of water was taken during emptying the filter tank, about 3 dm 3 The tested pollutant indicators were divided into basic (Fig. 2) and characteristic (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study also reported that the amount of CWG needed for filtration was 20% less than natural sand, showing greater economic benefit during handling, shipping, and disposal activities. Evans et al 136 studied the potential of CWG as a filter media to treat municipal potable water. It was observed that water quality obtained from CWG was similar to sand in terms of particle counts, turbidity, and metal content.…”
Section: In Water Filtration and Sandblastingmentioning
confidence: 99%